Upaya Guru dalam Meningkatkan Kualitas Pembelajaran Bahasa Arab - Qonita, Hilda, Drs. Abdullah Mahmud, M,Ag (2017)
Arabic language is a mean of communication existing in Arab Peninsula and Middle-East. Arabic is also a Quranic language namely kalam Allah and hadist. Learning the Arabic language has become one of the specialized subjectsin the educational institutions in both Islamic boarding schools ndconventional schools, but among them there are difficulties in Arabic language teaching and learning. One way to avoid this shortage is the need for breakthroughs of learning methods and evaluation of learning.Therefore, SMK Muhammadiyah 4 Surakarta has a new breakthrough in implementing Arabic language learning by applying the learning method of Arabic language which is active-learning, so that learning does not feel boring. Based on the background above, the researcher has tried to examine the efforts of teachers in improving the quality of learning Arabic in SMK Muhammadiyah 4 Surakarta. The problem to be studied in this research is what the teacher's efforts in improving the quality oflearning Arabic. The main purpose of this study is to describe the efforts of teachers in improving the quality of learning Arabic.This research is a field research because the data is taken directly from the field using descriptive qualitative method. The data collection methods used are observation, interview, and documentation.The observation is used to get the data directly from the process teachers do in learning Arabic, the method of learning Arabic and the geography of the school. The interview has been conducted with Muhammad Arif Agusnin as an Arabic teacher. The Documentation is used to overview data of SMK Muhammadiyah 4 Surakarta of the history of its establishment, school organization structure, vision, mission, purpose and infrastructure. The analytical method taken is descriptive qualitative analysis.In conclusion, the teacher's effortsin improving quality of learning Arabic include: 1) Grammar-Translation Method, 2) Direct Method, 3) Audio-Lingual Method, 4) Reading Method, 5) Cognitive Code Learning Method, 6) Total Physical Response, 7) Lecturing Method, 8) Discussion Method, andapplying the evaluation in the form of an oral test and a written test.Keywords: Arabic Language Learning, method, evaluation